Diseñar el plan estratégico para la empresa del sector construcción traing S.A.S. (2019)
The present work is elaborated with the purpose of designing a strategic plan for a company of the construction sector, dedicated to provide solutions in projects of design and construction of civil works in the Colombian public and private sector. In the first instance a theoretical review of the different organizational concepts applied in the strategic planning is carried out, simultaneously the information of the company is collected, where the mission, vision, objectives and current strategies are highlighted, identifying possible strengths and weaknesses that the company. In the second instance, possible opportunities and threats present in the external environment are identified and studied.